Assessment of Left Ventricular Function and Mitral Regurgitation Severity Early After Percutaneous Device Closure of the Atrial Septal Defect. Issue 1 (14th December 2021) - Sahebjam, Mohammad; Toofaninejad, Neda; Ajam, Ali; Hosseini, Kaveh; Jalali, Arash; Zoroufian, Arezou
Abstract : Background: Atrial septal defect (ASD) is one the most prevalent forms of congenital heart disease in adults. Closure of ASDs eliminates left-to-right shunt and reduces right heart volumes, but the effects of ASD closure, on the left ventricle (LV) and mitral valve competence are somewhat inconsistent. Therefore, we designed this study to evaluate the early effect of percutaneous closure of ASD on LV function and mitral regurgitation (MR) severity. Methods: In this prospective study, we enrolled 32 patients with ASD secundum who underwent percutaneous device closure in Tehran Heart Center. We used transthoracic and transesophageal echocardiography (TEE) before the procedure and TTE 24 hours after the procedure, then compared obtained LV parameters before and after the procedure. Results: LV end-diastolic diameter (LVEDD) increased significantly from 44.8 ± 2.4 to 45.8 ± 2.8 ( P < 0.001). LV end-systolic diameter (LVESD) also increased but was statistically insignificant ( P = 0.063) and LV ejection fraction (LVEF) remained nearly unchanged. Highest alteration was in right ventricular systolic pressure (12.4% decrease; P < 0.001) and mitral early Doppler/tissue Doppler velocity ratio (E/E′) (9.7% increase; P = 0.010). The change in MR severity was insignificant using Wilcoxon signed-rank test ( P = 0.157). Conclusions: We concluded that systolic functions do not change immediately. However, LVEDD and E/E′ will increase immediately, resulting from the passage of all blood from the LA into the LV in the early diastole just after closure. We also observed the positive effect of device closure on reducing right ventricular systolic pressure, and at least it does not worsen MR early after the procedure.